Literacy as Situated Practice - Li, Guofang (Canadian Journal of Education/Revue canadienne de l'éducation, 2001)
In this article, I examine the early literacy practices of a three-year-old Chinese girl in her family restaurant in an underprivileged community. Her literacy practices indicate that home contexts have a role in shaping emergent literacy. Her unique home literacy experiences, characterized by constructive, communal, and oral practices, are different from both school practices and those of middle-class Chinese immigrant families. Differences suggest a need for teachers to re-evaluate classroom practices to help minority children make the transition from their familiar world of home to the unfamiliar world of school. Une Chinoise de trois ans de milieu défavorisé apprend à lire et à écrire dans le restaurant familial. Cet apprentissage repose sur des pratiques constructives, collectives et orales différant des méthodes utilisées à l’école comme de celles des familles d’immigrants chinois de classe moyenne. Ces différences donnent à penser que les enseignants devraient réévaluer les méthodes d’apprentissage à l’école afin d’aider les enfants des minorités à faire la transition entre leur milieu familial et un monde qui ne leur est pas familier, à savoir l’école.